Program for Integrating Education for Sustainable Development (ESD) into Prospective Biology Teachers' Technological Pedagogical Content Knowledge (TPACK) - Purwianingsih, W.; Novidsa, I.; Riandi, R. (Jurnal Pendidikan IPA Indonesia, 2022)
This study aims to promote prospective biology teachers' Technological Pedagogical Content Knowledge (TPACK) about Education for Sustainable Development (ESD) or TPACK-ESD through a School Biology Course. The course is an integrated course as it discusses essential biology contents for the school and the strategies to present the content to the students. It is urgent to promote prospective teachers' TPACK-ESD since the existing biology teachers are not prepared to integrate ESD into biology lessons. The study applied a descriptive method based on a seven-step model of Reorient University Curricula to Address Sustainability (RUCAS). Participants in this study were third-year prospective teachers who were taking the course. The effectiveness of this program for prospective biology teachers is drawn from Content Representation (CoRes) and lesson plans prepared by prospective teachers. The results showed that prospective teachers' TPACK-ESD improved from early development to developed level. It means that prospective teachers' TPACK-ESD is still at a low level. Although the program can improve prospective biology teachers' competencies in developing lesson plans, the level is still low. One semester intensive program seems insufficient to promote prospective teachers' TPACK-ESD. Therefore, it is recommended that the program for promoting ESD integration into TPACK-ESD is conducted for an extended time. The novelty of this study lies in the findings and the coverage of the research area. This study is the first to explore a strategy to promote prospective teachers' TPACK-ESD. More studies are needed, especially on teachers' education curriculum and professional development programs, to accelerate the development of teachers' TPACK-ESD.